Congruency Analysis Of Task-Based Language Teaching (Tblt) And Primary School Standard Curriculum : From Policy To Textbook To Classroom Practice - Norany, Norhayu (2017)
This study investigates the fidelity of the curriculum policy (the planned curriculum), textbooks (the resourced curriculum) and classroom practices (the enacted curriculum) to the principles of TBLT in Malaysian primary ESL classrooms. The first phase of the research involved document analyses with the aim to investigate the extent to which the design of activities and activity cycles in recently published and officially mandated ESL Standard English Language Curriculum (SELC) textbooks for Malaysian primary schools reflect the principles of TBLT and key features of task design. The second phase of the research involves multiple case design to investigate how teachers implemented tasks from these textbooks, and the factors that influenced their pedagogic decision making. Findings from the research show that there is an alignment between policy and textbooks to TBLT principles.